2015
DOI: 10.1177/0007650315575040
|View full text |Cite
|
Sign up to set email alerts
|

Experienced Discrimination in Home Mortgage Lending: A Case of Hospital Employees in Northern Italy

Abstract: This article proposes a framework for the analysis of experienced discrimination in home mortgages. It addresses the problem of home mortgage lending discrimination in one of the richest areas of northern Italy. Employees of a local hospital were interviewed to study their perception (or experience) of discriminatory behavior related to home financing. The analysis follows two steps. The first evaluates self-selection (the probability that individuals apply) and the second focuses on the likelihood that applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…In this regard, it should be acknowledged that a preference towards an ethnicity may not always be due to positive sentiments associated with an ethnic group, but it could also relate to negative sentiments -negative stereotypes and prejudice -associated with other (minority) ethnic groups (Fossett, 2006). This ABM research seems to be consistent with empirical studies of economic conditions of residential settling where, for example, Secchi and Seri (2017b) found that gender and family size do not have a significant effect on segregation. Instead, the major factors affecting segregation (discrimination) was found to be nationality (foreign/native) and even the geographical segment of a country people belong to .…”
Section: Social/public Housingsupporting
confidence: 82%
“…In this regard, it should be acknowledged that a preference towards an ethnicity may not always be due to positive sentiments associated with an ethnic group, but it could also relate to negative sentiments -negative stereotypes and prejudice -associated with other (minority) ethnic groups (Fossett, 2006). This ABM research seems to be consistent with empirical studies of economic conditions of residential settling where, for example, Secchi and Seri (2017b) found that gender and family size do not have a significant effect on segregation. Instead, the major factors affecting segregation (discrimination) was found to be nationality (foreign/native) and even the geographical segment of a country people belong to .…”
Section: Social/public Housingsupporting
confidence: 82%
“…I therefore demonstrate a context in which firms are more likely to promote social justice and reduce economic inequality. These findings suggest increasing representation of minorities in lending decisions may reduce the effects of discrimination observed in other lending settings, such as mortgage lending in Italy (Secchi & Seri, 2017) and microfinance (Patel et al, in press).…”
mentioning
confidence: 93%